Muammoli amaliy mashg’ulotlarini tashkil etishda faol o’qitish usullaridan foydalanish xususiyatlari - Jamshed, Kosse RulenBekirovich (FILOLOGIYA UFQLARI JURNALI, 2021)
Annotation:In article under the name “The specification of organization problemthye lessons” are considering questions, levels of problem education creating problem situations, also necessity of the problem yeducation in present time.